Effectiveness of Tourism-Specialized Municipal Police in Maintaining Public Order at Tourist Destinations - I Dewa Gede Agung Putra Narayana; Nyoman Sri Subawa (PT ARRUS Intelektual Indonesia, 2026)
The Badung Regency has emerged as Bali's preeminent tourism hub, experiencing a substantial surge in visitorship following the pandemic. This has boosted the regional economy, but also led to overtourism, which threatens public peace and order in tourist destinations. The Badung Regency government set up a tourism police force to enforce local regulations and maintain security and order in tourist areas. The objective of this study is to analyze the effectiveness of the performance of the Tourism-Specific Municipal Police of Badung Regency in enforcing public peace and order in tourist destinations. The objective of the present study is to identify the factors that affect police performance. The study will offer solutions to existing obstacles. The present research employs a descriptive qualitative approach. The data presented herein were collected through a combination of in-depth interviews, field observations, and documentation studies. The informants were municipal police officers, relevant stakeholders, community members, and tourism business actors in tourist destinations. The analysis used an interactive model for data reduction, display, and conclusion drawing. The findings indicate that the performance of the Badung Regency's Tourism-Specific Municipal Police in maintaining public order in tourist destinations has not yet been fully effective. The condition is primarily influenced by human resource, facility, and infrastructure limitations, as well as insufficient foreign language skills. Nevertheless, a number of factors were identified that provided support for this hypothesis, including a clear regulatory framework, strong policy support from the local government, and cross-sectoral coordination. The study says that to improve security and order in tourist destinations in Badung Regency, more officers are needed.